2001
DOI: 10.1291/hypres.24.39
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Central Nervous System in the Development of Hypertension Produced by Chronic Nitric Oxide Blockade in Rats.

Abstract: We examined the role of the central nervous system, and particularly the renin-angiotensin (RA) system, in the development of hypertension produced by chronic inhibition of NO synthesis. In experiment 1, Wistar rats drank either nitro-L-arginine-methyl ester (L-NAME) or tap water. Before L-NAME treatment rats were divided into 6 groups. Four of them were administered either losartan or artificial cerebroventricular fluid (a-CSF) intracerebroventricularly (i.c.v.) for 1 week using an osmotic mini pump. The othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
1
4
0
1
Order By: Relevance
“…Similarly to our observations, in other models of hypertension, nNOS expression in the brain has been shown to be decreased or unchanged, and the decreases depend on the phase of development of hypertension (34)(35)(36). Second, recent studies have been shown that central nervous system mechanisms are involved in hypertension caused by chronic NOS inhibition (37,38). Eshima et al suggested that activation of the renin-angiotensin system in the NTS contributes to this neurogenic hypertension (38).…”
Section: Discussionsupporting
confidence: 86%
“…Similarly to our observations, in other models of hypertension, nNOS expression in the brain has been shown to be decreased or unchanged, and the decreases depend on the phase of development of hypertension (34)(35)(36). Second, recent studies have been shown that central nervous system mechanisms are involved in hypertension caused by chronic NOS inhibition (37,38). Eshima et al suggested that activation of the renin-angiotensin system in the NTS contributes to this neurogenic hypertension (38).…”
Section: Discussionsupporting
confidence: 86%
“…administration of angiotensin II (29), and chronic i.c.v. infusion of losartan attenuates the development of L-NAME hypertension (30).…”
Section: Fig 4 the Relationships Between Basal Map And Captopril-inmentioning
confidence: 97%
“…Elevated brain AngII binding sites have also been reported in spontaneously hypertensive fetal and newborn rats (47,48), and blockade of central RAS in adult spontaneously hypertensive rat can reverse their chronic hypertension (49). The underlying mechanisms and regulatory processes that lead to increased AT 1 receptor brain expression in 9% offspring are unknown but may involve a defect in nitric oxide pathway (27,50,51), positive feedback regulation by elevated brain AngII (52,53), and glucocorticoids (12,54,55).…”
Section: Table 2 Spectral Measurements Of Arterial Bpv In 9-to 12-wkmentioning
confidence: 99%